Optical and spin inhomogeneous linewidths in 171Yb3+:Y2SiO5 - Eloïse Lafitte-Houssat; Alban Ferrier; Sacha Welinski; Loïc Morvan; Mikael Afzelius; Perrine Berger; Philippe Goldner (Optical Materials: X, 2022)
Single crystals of 171Yb3+:Y2SiO5 are promising systems for quantum technologies as an efficient optical to spin interface. This is due to the long optical and spin coherence lifetimes, or narrow homogeneous linewidths, observed in this material at zero magnetic field. Inhomogeneous linewidths are also of importance since they affect peak absorption, available bandwidth or spin–spin interactions. In this work, we investigate inhomogeneous linewidths in a series of 171Yb3+:Y2SiO5 single crystals grown by the Czochralski method with the purpose of identifying the broadening mechanisms in the regime of ultra-low doping, i.e. in the ppm range. In a series of samples obtained with varying doping level, growth atmosphere, and cut at different locations in a crystal boule, optical inhomogeneous linewidths between 0.6 and 1.3 GHz are observed. This study suggests that these variations are due to changes in dislocation densities. Spin inhomogeneous linewidths, recorded using electron paramagnetic resonance, did not show the differences between samples observed in the optical domain. They were otherwise found to vary as a function of magnetic field orientation, enabling determination of directions that minimize e.g. detrimental spin–spin interactions. These results suggest ways to reduce optical inhomogeneous linewidths in 171Yb3+:Y2SiO5, which is of interest for high efficiency quantum memories and optical to microwave quantum transducers.